Investigating the Prevalence of Hepatitis B and C among Thalassemia Patients in Jahrom: A Cross-Sectional Descriptive Study - Vahid Mogharab (Journal of Global Pharma Technology, 2017)
Introduction: Thalassemia is a hereditary anemia which is inherited by the child from the parents. The prevalence of this disease is not equal in Iran. Blood products are used in order to treat thalassemia, especially thalassemia major, exposing the patients to the risk of infections including hepatitis B and C. Due to the vaccination against hepatitis B in thalassemia patients, its prevalence has been significantly decreased. However, hepatitis C is considered a prevalent disease, such that the hepatitis C virus can be claimed to be the most prevalent cause of chronic hepatitis in specific thalassemia groups. Therefore, the present study was conducted to investigate the prevalence of Hepatitis B and C among Thalassemia Patients in Jahrom. Method: This research was a cross-sectional descriptive study. In the present study, 167 patients with thalassemia in the Cooley's Ward of Shahid Motahhari Hospital were examined. Collected data included age, sex, duration of receiving the product, type of received product, type of thalassemia (major, intermedia), type of hepatitis (B, C), number of individuals with hepatitis, examination of the liver enzymes of individuals infected with hepatitis, and number of individuals who had undergone splenectomy. Data were analyzed in SPSS 11 using the chi-squared statistical test. Results: From among 167 thalassemia patients in the present study, 164 patients (98.2%) had thalassemia major and 3 patients (1.8%) had thalassemia intermedia.  Most cases of thalassemia (50 men and women, 60.24%) were found in the age group of 14-26 years. The prevalence of hepatitis B was 0% among thalassemia patients. The prevalence of hepatitis C was 7.93% (13 men and women) only among thalassemia major patients. The level of liver enzymes (AST, ALT) was higher among patients with hepatitis C compared with others. No significant relationship was observed between the number of cases with hepatitis C and age, sex, and times of blood transfusion (p>0.05).Conclusion: According to this study, the prevalence of hepatitis B and C was low among thalassemia patients in Jahrom.Keywords: Hepatitis B, Hepatitis C, Thalassemi.